On the problem of abbreviation as a means of linguistic economy (upon the material of the english literary text “report from iron mountain on the possibility & desirability of peace”) - Мілова, Маргарита; Мілова, М. М.; Milova, Margarita (Analele Universităţii din Craiova, 2022)
У статті висвітлюються теоретичні уявлення про роль і місце абревіатур, а також описуються структурно-семантичні особливості абревіатурної лексики. Вона спрямована на розробку системного підходу до вивчення цього явища на матеріалі англомовного художнього тексту шляхом визначення типів акронімів в англійській мові на основі умовного, загальновживаного, аналізу системних, структурних, семантичних характеристик скороченого слова. лексику англійської мови та спробу встановити основні структурно-семантичні характеристики такої лексики.

The article throws light upon the theoretical understanding of the role and place of abbreviations, as well as the description of the structural and semantic features of the abbreviation vocabulary. It aims at developing a systematic approach to the study of this phenomenon on the material of an English literary text by defining the types of acronyms in English on the basis of conventional, common usage, analysis of the systemic, structural, semantic characteristics of the abbreviated vocabulary of English and by trying establish the basic structural-semantic characteristics of such vocabulary.
До проблеми абревіації як засобу лінгвістичної економії (на матеріалі англомовного художнього тексту «звіт із залізної гори про можливість та бажаність миру»
Milova M. On the problem of abbreviation as a means of linguistic economy (upon the material of the english literary text “report from iron mountain on the possibility & desirability of peace”) / Margarita Milova // Analele Universităţii din Craiova. Seria Ştiinţe Filologice. Lingvistică. – Anul XLIV. – Nr. 1-2. – 2022. –- PP. 109-123. https://doi.org/10.52846/aucssflingv.v44i1-2.54
Keywords: Research Subject Categories::SOCIAL SCIENCES; абревіація; система мови; структурно-семантична характеристика; abbreviation; language system; structural and semantic characteristics